2011
DOI: 10.1063/1.3541818
|View full text |Cite
|
Sign up to set email alerts
|

Droplet charging regimes for ultrasonic atomization of a liquid electrolyte in an external electric field

Abstract: Distinct regimes of droplet charging, determined by the dominant charge transport process, are identified for an ultrasonic droplet ejector using electrohydrodynamic computational simulations, a fundamental scale analysis, and experimental measurements. The regimes of droplet charging are determined by the relative magnitudes of the dimensionless Strouhal and electric Reynolds numbers, which are a function of the process ͑pressure forcing͒, advection, and charge relaxation time scales for charge transport. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For the solvents and electric eld strengths considered here, the electric timescales, i.e., charge relaxation and ion transit, were sufficiently shorter than the hydrodynamic timescales, leading to a quasi-electrostatic limit of the electrohydrodynamics and direct correlation between electric eld and droplet charge. [49][50][51] The signal saturation relationship experienced at elevated potentials has also been demonstrated with emitted current measurements and found to be a result of droplet discharging effects at the DEFFI orice for high applied potentials, as the electrospraying regime was approached. 23,47 The maximum achievable emitted current due to orice discharging effects corresponded directly with the local maxima cocaine signal intensity (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…For the solvents and electric eld strengths considered here, the electric timescales, i.e., charge relaxation and ion transit, were sufficiently shorter than the hydrodynamic timescales, leading to a quasi-electrostatic limit of the electrohydrodynamics and direct correlation between electric eld and droplet charge. [49][50][51] The signal saturation relationship experienced at elevated potentials has also been demonstrated with emitted current measurements and found to be a result of droplet discharging effects at the DEFFI orice for high applied potentials, as the electrospraying regime was approached. 23,47 The maximum achievable emitted current due to orice discharging effects corresponded directly with the local maxima cocaine signal intensity (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…For these conditions, excitation signal amplitudes below 10 V pp did not yield the necessary liquid velocity in the nozzle orifice to achieve ejection. The positive polarity of the measured current was due to net positive charge transport through advection and migration of hydrogen ions in an alternating current electric field induced by the signal actuating the piezoelectric transducers . Figure (b) also displays the ejected droplet stream below the ultrasonic nebulizer for a range of signal amplitudes.…”
Section: Resultsmentioning
confidence: 66%
“…These systems readily atomize liquid samples for further droplet desolvation and introduction of analyte into the gas phase, and require little to no sample preparation. They also induce droplet charging and analyte ionization through inherent electric fields generated by the piezoelectric element actuation, by the application of external electric fields, or through coupling techniques such as extractive electrospray ionization (EESI) . EESI enables the ionization of neutral analytes from the gas phase, liquid phase, or from atomized aerosols .…”
mentioning
confidence: 99%
“…Although the behavior of liquid droplets under the action of electrohydrodynamic forces has been studied since the early 20 th century, several issues remain topics of theoretical study. [ 70,71 ] Basaran and co-workers developed modeling approaches for EHD tip-streaming from a fi lm [ 72 ] and a droplet [ 22 ] to capture the mechanisms of drop formation and the associated scaling laws. In a recent study, [ 22 ] they demonstrated the existence of three different regimes for the size and charge of droplets depending on the conductivity of the fl uid.…”
Section: Modeling Studiesmentioning
confidence: 99%
“…An enhanced fundamental understanding and computational models that can simulate the jet formation process will be needed for the practical use of e‐jet printers in routine nanomanufacturing. Although the behavior of liquid droplets under the action of electrohydrodynamic forces has been studied since the early 20 th century, several issues remain topics of theoretical study . Basaran and co‐workers developed modeling approaches for EHD tip‐streaming from a film and a droplet to capture the mechanisms of drop formation and the associated scaling laws.…”
Section: Jet Formation and Important Factorsmentioning
confidence: 99%